PENERAPAN MODEL KOOPERATIF LISTENING TEAM UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PADA MATA KULIAH KIMIA FISIKA I - Maria Erna (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2016)
It has been applied the cooperative learning model Listening Team to improve thequality of learning in Physical Chemistry I Course on the first semester of the academicyear 2014/2015. The research is a pre-experimental research with single one shot casestudy and one group pretest-posttest design. The research results showed that theapplication of cooperative learning model Listening Team can improve the quality oflearning in the Course of Physical Chemistry I. The results of the quality of the learningprocess on the subjects of Physical Chemistry I showed that the interaction of studentswith learning resources are positive trend. The average value of Task Sheet To Students(TSS) was over than 80 for each meetings and group awards varies for each meeting.The competence or ability of students obtained based on the assessment of learningoutcomes are an average N-Gain value by 0.55 into in improvement the mediumclassification and the mastery level in classical by 60%.Keywords: Cooperative, Learning, Listening Team, Physical Chemistry I, Quality